REVIEW ARTICLE ON EFFECT OF STEROID MEDICATION AND RELATED ADVERSE DRUG REACTION IN ELDERLY PEOPLE - Sanju Kharel, Sepideh Shadvar*, Hamed Barzeh (Journal of Biomedical and Pharmaceutical Research, 2017)
Drug-related problems are a very common issue in the elderly patient and include drug ineffectiveness, adverse drug effects, overdosage, under dosage and drug interactions. Adverse drug effects are effects that are unwanted, uncomfortable or dangerous. Common examples are oversedation, confusion, hallucinations, falls and bleeding. Among ambulatory people ≥ 65, adverse drug effects occur at a rate of about 50 events per 1000 person-years. Hospitalization rates due to adverse drug effects are 4 times higher in the aged patients (about 17%) than in younger patients (4%). Glucocorticoids (GCs) often referred to as corticosteroids are synthetic steroids but naturally and biologically, they are active derivatives, secreted from cortisol by the adrenal cortex. Corticosteroids are used as powerful medications but they can have very wide range of side effects. So we can use them only if the potential benefits are outweighing this risk. The risk of experiencing side effects largely depends on: a) the dose (higher dose shows a greater risk of developing of side effects). b) The type of steroid (steroid tablets are more likely to cause side effects than inhalers or injections). c) The length of treatment (if the patient takes steroid tablets for more than three weeks). d) Age, (young children and the elderly are more likely to experience side effects). Keywords: corticosteroids, adverse drug reactions, ageing